Why software fails [software failure]. - Charette, R.N.
Most IT experts agree that software failures occur far more often than they should despite the fact that, for the most part, they are predictable and avoidable. It is unfortunate that most organizations don't see preventing failure as an urgent matter, even though that view risks harming the organization and maybe even destroying it. Because software failure has tremendous implications for business and society, it is important to understand why this attitude persists.
Keywords: Failure prevention; Project management; Risk management; Software failure; Software projects management